Characterization of the collagen component of cartilage repair tissue of the talus with quantitative MRI: comparison of T2 relaxation time measurements with a diffusion-weighted double-echo steady-state sequence (dwDESS) - Kretzschmar, Martin; Miska, Matthias (European radiology, 2014)
OBJECTIVES: The purpose of this study was to characterize the collagen component of repair tissue (RT) of the talus after autologous matrix-induced chondrogenesis (AMIC) using quantitative T2 and diffusion-weighted imaging. METHODS: Mean T2 values and diffusion coefficients of AMIC-RT and normal cartilage of the talus of 25 patients with posttraumatic osteochondral lesions and AMIC repair were compared in a cross-sectional design using partially spoiled steady-state free precession (pSSFP) for T2 quantification, and diffusion-weighted double-echo steady-state (dwDESS) for diffusion measurement. RT and cartilage were graded with modified Noyes and MOCART scores on morphological sequences. An association between follow-up interval and quantitative MRI measures was assessed using multivariate regression, after stratifying the cohort according to time interval between surgery and MRI. RESULTS: Mean T2 of the AMIC-RT and cartilage were 43.1 ms and 39.1 ms, respectively (p = 0.26). Mean diffusivity of the RT (1.76 μm(2)/ms) was significantly higher compared to normal cartilage (1.46 μm(2)/ms) (p = 0.0092). No correlation was found between morphological and quantitative parameters. RT diffusivity was lowest in the subgroup with follow-up >28 months (p = 0.027). CONCLUSIONS: Compared to T2-mapping, dwDESS demonstrated greater sensitivity in detecting differences in the collagen matrix between AMIC-RT and cartilage. Decreased diffusivity in patients with longer follow-up times may indicate an increased matrix organization of RT. KEY POINTS: • MRI is used to assess morphology of the repair tissue during follow-up. • Quantitative MRI allows an estimation of biochemical properties of the repair tissue. • Differences between repair tissue and cartilage were more significant with dwDESS than T2 mapping.